Negative equity in Ireland: estimates using loan-level data. Issue 3 (28th October 2014) - Gibb, Kenneth; Marsh, Alex; Duffy, David; O'Hanlon, Niall
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – This paper aims to, using a unique loan-level data set, show the extent to which negative equity in Ireland is concentrated in younger age groups. The sharp decline in house prices since 2007 has led to the emergence of widespread negative equity in Ireland. However, little is known about the type of borrower experiencing negative equity. Design/methodology/approach – This paper uses a unique data set that, for a large sample of mortgages, provides details on both the characteristics of the borrowers and their mortgages. Using this data set, the paper estimates the incidence of negative equity by analysing loans taken out to purchase a primary residence in the period 2005-2012. Findings – The analysis finds the situation in Ireland to be much more severe than that being experienced in other housing market downturns at present, with 64 per cent of borrowers in the period 2005-2012 experiencing negative equity. Analysis by age gives rise to concern, with the majority of those in negative equity aged under 40 years. The paper also points to the large wealth loss experienced by Irish households, in the order of 43 billion, as a result of the fall in property values. Originality/value – The paper is one of the first using loan-level time-series data in Ireland. It highlights the growth in negative equity during the crisis and the extent to which it is concentrated in the younger age groups. It also provides an estimate of the loss in wealth suffered by all households due to the fall in Irish house prices.